Zdravila za zdravljenje benigne hiperplazije prostate - Ilaš, Janez (Farmacevtski vestnik, 2014)
The most important synthetic drugs used for treating benign hyperplasia of prostate are presented in the article. Active ingredients of two pharmacological groups are almost exclusively used, alpha-adrenoreceptor antagonists and testosterone-5-alpha reductase inhibitors. Briefly, some drugs, recently described in scientific and professional literature for the relief of symptoms are also mentioned.
Keywords: alpha-adrenoreceptor antagonists; antagonisti adrenergičnih receptorjev alfa; benign hyperplasia of prostate; benigna hiperplazija prostate; lajšanje težav; testosterone 5-alpha reductase inhibitors; zaviralci testosteron-5-alfa reduktaze